2019
DOI: 10.1038/s41590-019-0477-z
|View full text |Cite
|
Sign up to set email alerts
|

A protective Zika virus E-dimer-based subunit vaccine engineered to abrogate antibody-dependent enhancement of dengue infection

Abstract: Infections with dengue virus (DENV) and Zika virus (ZIKV) can induce cross-reactive antibody responses. Two immunodominant epitopes—one to precursor membrane protein and one to the fusion loop epitope on envelope (E) protein—are recognized by cross-reactive antibodies1–3 that are not only poorly neutralizing, but can also promote increased viral replication and disease severity via Fcγ receptor-mediated infection of myeloid cells—a process termed antibody-dependent enhancement (ADE)1,4,5. ADE is a significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 52 publications
1
48
0
Order By: Relevance
“…Recently, a characterization of two dimeric E antigens was published, dimerization was achieved by the A264C mutation or replacing the E transmembrane domain with the FC fragment of a human IgG (39). While this manuscript was under preparation, two other articles reported development and evaluation of dimer-based subunit vaccines similar to that described in here (40,41). The authors showed that in all three cases the antigens were able to induce in mice the production of neutralizing antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a characterization of two dimeric E antigens was published, dimerization was achieved by the A264C mutation or replacing the E transmembrane domain with the FC fragment of a human IgG (39). While this manuscript was under preparation, two other articles reported development and evaluation of dimer-based subunit vaccines similar to that described in here (40,41). The authors showed that in all three cases the antigens were able to induce in mice the production of neutralizing antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, cross-linking of two E80 proteins through additional disulfate bonds in domain II and domain III could stabilize the anti-parallel structure of the soluble E80 dimer, limiting the exposure of fusion-loop, but enabling the presentation of cross-serocomplex broadly neutralizing EDE epitopes (Rouvinski et al, 2017; Figure 1B). Consistently, in a recent study, the covalently stabilized ZIKV E dimer has successfully elicited protective antibody responses against ZIKV infection in mice, without causing cross-reactivity to dengue viruses or ADE of DENV (Slon-Campos et al, 2019). Currently, both Zika EDIII and Dengue tetravalent EDIII vaccines are under development.…”
Section: Universal B Cell Vaccines For Denv and Zikvmentioning
confidence: 67%
“…Besides, other forms of ZIKV vaccine, such as protein based subunit vaccine (Medina et al, 2018;Metz et al, 2019;Slon-Campos et al, 2019) and live attenuated Zika vaccines (Richner et al, 2017b;Xie et al, 2018;Shan et al, 2019) are also under development at the pre-clinical stage. Considering the crossreactivity and ADE between ZIKV and DENV, newly developed ZIKV vaccine should also be tested for DENV enhancement activity.…”
Section: Zika Vaccines In Clinical Trialsmentioning
confidence: 99%
“…To model a rapid response to a previously known pathogen, we used a mAb discovery approach that assumed the envelope protein (ZIKV E protein) on the virion surface is a key protective antigen 5,6,21,22 . We used memory B cells from previously infected human subjects as the source for antibody discovery ( Supplementary Table 1 ).…”
Section: Resultsmentioning
confidence: 99%